Cushing’s syndrome as a rare manifestation of adrenal tumours in infants – case report - Badurowicz, Jagoda; Stefanowicz, Joanna; Jezierska, Michalina; Janecka, Aleksandra; Birkholz-Walerzak, Dorota; Gołębiewski, Andrzej; Piskunowicz, Maciej; Świętoń, Dominik (Pediatria Polska - Polish Journal of Paediatrics, 2019)
We report a case of a six-week-old male infant with a congenital tumour of the left suprarenal gland. The tumour was diagnosed by ultrasound examination (USG) as a neonatal suprarenal mass. By the third month of life, the patient had typical signs of Cushing’s syndrome. Based on the results of hormonal tests and imaging studies (USG and MRI), an adrenocortical tumour was suspected. The patient could only be cured by surgery. Histopathological examination confirmed clinical diagnosis of an adrenocortical tumour. We concluded that Cushing’s syndrome may be a rare clinical manifestation of adrenal tumour in neonates. Only careful observation allows for proper diagnosis and appropriate treatment. Correct diagnosis is essential for optimal postnatal treatment.